Abundance and Frequency of the Asiatic Oak Weevil (Coleoptera: Curculionidae) and Defoliation on American, Chinese, and Hybrid Chestnut (Castanea). Issue 1 (21st March 2016) - Case, Ashley E.; Mayfield, Albert E.; Clark, Stacy L.; Schlarbaum, Scott E.; Reynolds, Barbara C.
Abstract: The Asiatic oak weevil, Cyrtepistomus castaneus Roelofs (Coleoptera: Curculionidae), is a nonnative defoliator of trees in the Fagaceae family in the United States but has not been studied on Castanea species in the southern Appalachian Mountains. Planted trees of Castanea dentata (Marsh.) Borkh. (Fagales: Fagaceae), Castanea mollissima Blume (Fagales: Fagaceae), and four hybrid breeding generations were evaluated in 2012 for insect defoliation and C. castaneus abundance and frequency. Defoliation was visually assessed throughout the growing season at two sites in the southern Appalachian Mountains (western North Carolina and eastern Tennessee). C. castaneus abundance and frequency were monitored on trees using beat sheets and emergence was recorded from ground traps. Asiatic oak weevils were more abundant and more frequently collected on American chestnut ( Ca. dentata ) and its most closely related BC3 F3 hybrid generation than on the Asian species Ca. mollissima. In most months, C. castaneus colonization of hybrid generations was not significantly different than colonization of parental species . Frequency data for C. castaneus suggested that adults were distributed relatively evenly throughout the study sites rather than in dense clusters. Emergence of C. castaneus was significantly higher under a canopy dominated by Quercus species than under non- Quercus species or open sky. C. castaneus emergence began in May and peaked in late June and early July. These results may be useful for resource managers trying to restore blight-resistant chestnut to the Southern Appalachians while minimizing herbivory by insect pests.